Long-term Effects of Biosolids on Soil Quality and Fertility. Issue 3 (May 2018) - Nicholson, Fiona; Bhogal, Anne; Taylor, Matt; McGrath, Steve; Withers, Paul
Abstract : ABSTRACT: Biosolids are an important potential source of plant-available nutrients and also contain valuable quantities of stable organic matter, which can provide long-term benefits to soil structure and fertility. In this study, the long-term impacts of biosolids recycling to agricultural land on soil quality and fertility were assessed using established experimental platforms at four sites in England with contrasting soil types and agroclimatic conditions. At each site, treatment plots that had received 20 annual additions of biosolids (i.e., three types of digested sludge cake) at rates of 2.9 to 3.4 t ha −1 y −1 since 1994 were used in comparison with an untreated control treatment (which had received inorganic fertilizers only) to quantify the effects of biosolids on soil physical, chemical, and biological properties. Significant increases ( P < 0.05) in soil organic matter (SOM) of 10% to 17% and in "light fraction" SOM (up to 2.9 mg kg −1 on the biosolids treatment compared with 1.8 mg kg −1 on the untreated control), along with a significant ( P < 0.01) increase of up to 10% in available water capacity and numerical increases in water infiltration rate and aggregate stability, were found in plots that received biosolids. These plots also had significant ( P < 0.05) increases of up to 20%, 48%, and 30% in soil total nitrogen, extractable phosphorus, and total sulfur, respectively. Earthworm numbers and weights were approximately doubled relative to the untreated control ( P < 0.05) where low-metal biosolids had been applied. These results indicate that applying biosolids to agricultural land is an important means of replenishing and maintaining SOM levels. Importantly, no adverse effects on crop quality were observed. The results from this study provided valuable evidence toward maintaining a sustainable agricultural landbank for biosolids recycling in the United Kingdom.